Pharmacogenetics and pharmacogenomics of immunosuppressive agents: perspective for individualized therapy. (1st December 2004) - Cattaneo, Dario; Tankiewicz, Anna; Merlini, Simona; Perico, Norberto; Remuzzi, Giuseppe
Immunosuppressive therapy has markedly improved over the past years with the advent of highly potent and rationally targeted immunosuppressive agents. Since these drugs are characterized by a narrow therapeutic index, major efforts have been carried out to define therapeutic windows based on the blood levels of each immunosuppressant, and relating those concentrations to clinical events. Although pharmacokinetic-based approaches are currently used as useful tools to guide drug dosing, they present several limitations. Pharmacogenomics –– a science that studies the inherited basis of differences between individual responses to drugs in order to identify the best dose and therapy for each patient –– might represent a complementary support. Preliminary studies that have focused on polymorphisms of genes encoding enzymes involved in drug metabolism, drug distribution, and pharmacological target, have shown promising results. Indeed, pharmacogenomics holds promise for improvement in the ability to individualize pharmacological therapy based on the patient''s genetic profile.